ENHANCING EOCB THROUGH DPJ-FIT: RECENT RESEARCH IN THE HOSPITAL NURSES ENVIRONMENT - Ranihusna, Desti; Paramita, Eudiena Pradnya (Universitas PGRI Semarang, 2023)
The aim of this study is to test how much influence Environmental Organizational Citizenship Behavior (EOCB) has directly from Digital Person-Job Fit (DPJ-Fit) and indirectly through Job Satisfaction (JS). This research is the recent research on OCB in the hospital nurse’s environment. This study employed a population of nurses in type C hospitals with a sample of 209 people. The type of sampling technique in this study applied simple random sampling. Multivariate data analysis techniques or Structural Equation Modeling (SEM) were implemented with analysis tools using Partial Least Square software (Smart PLS 3.0). The results showed that DPJ-Fit directly and indirectly affects EOCB. The greater influence on EOCB is through the mediating role of JS. Further research may allow Job Satisfaction for similar research.